Comparison of three malnutrition risk screening tools in identifying malnutrition according to Global Leadership Initiative on Malnutrition criteria in gastrointestinal cancer - Huang, Yangyang; Chen, Ying; Wei, Lu; Hu, Yan; Huang, Liya (Frontiers in Nutrition, 2022)
Background: Malnutrition is common in patients with gastrointestinal cancer. The first step in the diagnosis of malnutrition is to evaluate the malnutrition risk by validated screening tools according to the Global Leadership Initiative on Malnutrition (GLIM). This study aimed to determine the best nutritional screening tool for identifying GLIM malnutrition, and validate the performance of these tools in different age subgroups. Methods: We did a prospective cohort study of patients who were diagnosed with gastrointestinal cancer from February 2016 to November 2019. The sensitivity, specificity, positive predictive values (PPV), negative predictive values (NPV) and area under the ROC curve (AUC) of three screening tools (NRS 2002, GNRI, MNA-SF) were calculated. Results: A total of 488 patients were enrolled, and 138 patients (28.27%) were malnutrition according to the GLIM criteria. The consistency of NRS 2002, GNRI, MNA-SF with GLIM-defined malnutrition was 74.8%, 72.1%, and 71.1%, respectively. In subgroup analysis of young patients (<65 years), NRS 2002 exhibited best discrimination with the AUC of 0.724 (95% CI, 0.567-0.882), the sensitivity of 64.3% (95% CI, 35.6-86.0), and the specificity of 80.6% (95% CI, 69.2-88.6). In patients older than 65 years, MNA-SF exhibited best discrimination with the AUC of 0.764 (95% CI, 0.714-0.814), the sensitivity of 82.3% (95% CI, 74.1-88.3), and the specificity of 70.5% (95% CI, 64.7-75.7). Conclusions: NRS2002 is the best malnutrition screening tool in gastrointestinal cancer patients younger than 65 years, and MNA-SF is the best malnutrition screening tool in patients older than 65 years. It is necessary to select targeted nutritional screening tools according to the difference of age.